Differential in infant, childhood and under-five death clustering among the empowered and non-empowered action group regions in India - Ronak Paul; Rashmi Rashmi; Shobhit Srivastava (BMC, 2021)
Abstract Background With 8,82,000 deaths in the under-five period, India observed varied intra-state and inter-regional differences across infant and child mortality in 2018. However, scarce literature is present to capture this unusual concentration of mortality in certain families by examining the association of the mortality risks among the siblings of those families along with various unobserved characteristics of the mother. Looking towards the regional and age differential in mortality, this paper attempts to provide evidence for the differential in mortality clustering among infants (aged 0-11 months), children (12-59 months) and under-five (0-59 months) period among mothers from the Empowered Action Group (EAG) and non-EAG regions of India. Methods The study used data from the National Family Health Survey (2015-16) which includes all the birth histories of 475,457 women aged 15-49 years. Bivariate and multivariate analyses were used to fulfil the objectives of the study. A two-level random intercept Weibull regression model was used to account for the unexplained mother (family) level heterogeneity. Results About 3.3% and 5.9% of infant deaths and 0.8% and 1.6% of childhood deaths were observed in non-EAG and EAG regions respectively. Among them, a higher percentage of infant and child death was observed due to the death of a previous sibling. There were 1.67 times [95% CI: 1.55-1.80] and 1.46 times [CI: 1.37-1.56] higher odds of infant and under-five mortality of index child respectively when the previous sibling at the time of conception of the index child was dead in the non-EAG regions. In contrast, the odds of death scarring (death of previous sibling scars the survival of index child) were 1.38 times [CI: 1.32-1.44] and 1.24 times [CI: 1.20-1.29] higher for infant and under-five mortality respectively in the EAG regions. Conclusion The extent of infant and child mortality clustering and unobserved heterogeneity was higher among mothers in the non-EAG regions in comparison to their EAG region counterparts. With the growing situation of under-five mortality clustering in non-EAG states, region-wise interventions are recommended. Additionally, proper care is needed to ameliorate the inter-family variation in mortality risk among the children of both EAG and non-EAG regions throughout their childhood.